ANALISIS KELAYAKAN FINANSIAL DAN NON FINANSIAL USAHA AGROINDUSTRI KOPI : (Studi Kasus Pada Home Industri Casim Coffe Kabupaten Jember) - Rara Iftinan Julianti; Fredy Eka Ardhi Pratama (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The Casim Coffe business is a coffee processing business located in Karang Pring village and uses coffee beans as its main raw material. Every year coffee beans always experience price increases which cause business disruptions. This study aims to analyze the financial and non-financial feasibility of the Cash Coffee business. The financial aspect is seen from the four criteria, namely NPV, IRR, PI or Net B/C and Payback Period. The NPV value obtained is IDR 366,069,410, the IRR value obtained is 26.79%, the B/C value obtained is 2.03, and the payback period is 2 years and 2 months. On the non-financial aspects seen from technical aspects, legal aspects, social and economic aspects, environmental aspects, market aspects. The results of the study show that Casim Coffe's business is feasible from a financial and non-financial perspective, except for the environmental aspect where Casim Coffe's business needs to process liquid waste so as not to damage the surrounding environment. The results of the sensitivity analysis conducted on Casim Coffe's business show that Casim Coffe's business is sensitive to changes in raw material prices and product sales prices.